KL2 scholars’ perceptions of factors contributing to sustained translational science career success - Susan S. Smyth; Barry S. Coller; Rebecca D. Jackson; Philip A. Kern; Scott McIntosh; Emma A. Meagher; Doris M. Rubio; Kathryn Sandberg; Joel Tsevat; Jason G. Umans; Jacqueline Attia; Heather L. Baker; et al. (Journal of Clinical and Translational Science, 2022)
Abstract